The Morphological Traits of Brazilian Spinach on Different Shading intensi-ties and Organic Fertilizer - Strayker, Ali Muda; Fitra , Gustiar; Theresia , Aprila Sareng; Zaidan , Panji Negara; Erizal , Sodikin; Entis Sutisna , Halimi (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2025)
Environmental growth will have an impact on plant morphology. This condition also involves shading and nutrient availability for Brazilian spinach as an introduced leafy vegetable. The study aimed to evaluate Brazilian spinach growth and yield on different shading intensities and organic fertilizers. The study adopted a split-plot design with artificial shading intensities (0%, 50%, and 70%) as the main plot and the type of organic fertilizer (guano, vermicompost, liquid organic fertilizer) as the subplot. The results showed that Brazilian spinach could adapt to canopy areas. However, the Brazilian spinach growth was dominant in a no-shade environment (S0). It was evident by shoot fresh weight (SFW), stem dry weight (SDW), branch dry weight (BDW) and leaf dry weight (LDW). Guano fertilizer (F1) was an organic fertilizer that increased the observed variables, including canopy growth, nutrient and water absorption ability and absolute growth of Brazilian spinach. Although the shoot-root ratio for each single treatment did not show a significant effect. There was a significantly interaction between shade and organic fertilizer in Brazilian spinach growth for all morphological traits including shoot-root ratio. Generally, leaf growth was a positive correlation to stem (R2= 0.9918), branches (R2= 0.7258) and shoots (R2=0.9105). In conclusion, the most suitable growing environment for Brazil spinach growth and yield is in no-shading areas, while guano fertilizer application is recommended to be selected to enhance Brazil spinach growth and yield.